2014
DOI: 10.1021/jp507364h
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale B3LYP Simulations of Ibuprofen Adsorbed in MCM-41 Mesoporous Silica as Drug Delivery System

Abstract: The atomistic details of the interaction between ibuprofen (one of the most common nonsteroidal anti-inflammatory drugs) and a realistic model of MCM-41 (one of the most studied mesoporous silica materials for drug delivery) were elucidated by quantum mechanical modeling inclusive of London forces. Calculations are based on periodic density functional theory adopting all-electron Gaussian-type basis functions of polarized double-ζ quality and the B3LYP hybrid functional. By docking the drug on different sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 63 publications
4
60
0
Order By: Relevance
“…The shielding tensor is computed using the GIPAW 34 approach which permits the reproduction of the results of a fully converged all-electron calculation. Absolute shielding tensors are obtained and the 13 C scale was fixed so that experimental 35 and calculated chemical shifts of all carbon sites in bulk ibuprofen 36 coincide.…”
Section: Ab Initio Calculations Of Nmr Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The shielding tensor is computed using the GIPAW 34 approach which permits the reproduction of the results of a fully converged all-electron calculation. Absolute shielding tensors are obtained and the 13 C scale was fixed so that experimental 35 and calculated chemical shifts of all carbon sites in bulk ibuprofen 36 coincide.…”
Section: Ab Initio Calculations Of Nmr Parametersmentioning
confidence: 99%
“…A very complete study by the group of Ugliengo [13][14] , presented a new realistic model for MCM-41, introducing hybrid functionals corrected for dispersion forces. They showed that electronic dispersion contributions to the interaction are critical for the correct description of the interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The surface is represented by a realistic model of hydroxylated amorphous silica layers as designed by Ugliengo et al [14] exhibiting a surface OH density of 4.5 nm −2 , a thickness of 7.2 Å and a surface area per unit cell of 161.8 Å 2 [15]. All the calculations reported in the manuscript are performed with the public version of the program Crystal [12,16] for ab initio quantum chemistry of solid state.…”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
“…It seems evident that the driving force, promoting the anchor on the surface despite the sensitive strain on both the molecule and the surface adsorption layer, is the possibility to form strong and cooperative hydrogen bonds. Such opportunity is maximized in the case of the configuration 1 which results the most thermodynamically stable also at room temperature, as shown in the last column of Table 1, where differences in the standard Gibbs free energies, thus including the zero point energy and the temperature-dependent vibrational contributions to both energy and entropy, are reported [15]. Then, to model a more diluted coverage as representative of the correct experimental situation, a 2 × 2 supercell (with a surface area of 647.2 Å 2 ) was designed starting from aggregate 1.…”
Section: Quercetin Adsorptionmentioning
confidence: 99%
“…Quantum-mechanical simulations can give some insight on the issue, by providing geometries of adsorption, energetics and by predicting experimental observables (e.g., infrared spectra). In the past years, we have extensively investigated the interaction between ibuprofen, as a model of all propionic acid derivatives, and silica, using both surface models [12] and a realistic model for the MCM-41 mesoporous material [13], also simulating the effect of air humidity on the system [14].…”
mentioning
confidence: 99%